Relationship of age and scrotal circumference with the seminal characteristics of crossbred bulls - SUDHEER, S (The Indian Journal of Animal Sciences, 2014)
Ejaculates (562) were collected from 27 crossbred bulls aging 24 to 88 months to study the relationship of age and scrotal circumference on the seminal characteristics of bulls, Based on age and scrotal circumference, the bulls were divided into 3 groups respectively, There was a significant (P<0.05) increase in scrotal circumference, ejaculate volume and total sperm output in group 3 (>56m) compared to group 2 (44-56m) and group 1 (<44m), The ejaculate volume, total sperm output and per cent of live sperms was significantly (P<0,05) higher in group 3 (>35cm) than that in group 2 (30-35cm) and group 1 (<30cm), Nonsignificant differences in initial motility, sperm concentration/ml of ejaculate, total abnormal sperms and post-thaw revival rates were observed among the groups,